The prevalence and associated factors of dysphagia in Parkinson's disease: A systematic review and meta-analysis - Gong, Siyuan; Gao, Yan; Liu, Jihong; Li, Jia; Tang, Xueqin; Ran, Qian; Tang, Rongzhu; Liao, Chunlian (Frontiers in Neurology, 2022)
Background The prevalence and associated factors of dysphagia in Parkinson's disease (PD) are different in studies conducted in different countries. The purpose of our systematic review and meta-analysis was to evaluate the prevalence of dysphagia in PD and to clarify its associated factors. Methods Two researchers systematically searched PubMed, Embase, Web of Science, Cochrane Library, CNKI, Wanfang Database, SinoMed and VIP databases and manually searched references in the retrieved articles to identify potential research subjects. The last search was conducted on June 28, 2022. Finally, a total of 58 studies including 60 observations with 20,530 PD patients were included in our meta-analysis. Results The meta-analysis estimated that the pooled prevalence rate of dysphagia in PD was 36.9% (95% CI: 30.7–43.6%) and instrumental examination showed a higher prevalence (57.3%, 95% CI: 44.3–69.1%). Oceania showed the highest prevalence of dysphagia in PD (56.3%) compared to Africa (39.5%), Asia (38.6%), Europe (36.1%) and America (28.9%). Dysphagia in PD was associated with older age, lower body mass index, longer disease duration, higher Hoehn and Yahr stage and levodopa equivalent daily dose, PIGD subtype, severe motor symptoms, drooling and higher levels of depression, and lower quality of life. Conclusions In conclusion, our meta-analysis showed that dysphagia occurs in more than one-third of PD patients and was associated with several demographic characteristics and PD-related characteristics, motor symptoms, non-motor symptoms, as well as decreased quality of life. It deserves early screening, diagnosis, and treatment in clinical practice to prevent serious complications from dysphagia.